Pion-nucleon resonances and the angular distribution in pion electroproduction - Jones,HF (Il Nuovo Cimento A, 1965)
Using the helicity formalism, we find the contributions from final states of definite spin and parity, together with the interference terms between different final-state contributions, to the angular distributions of pions electro-produced from protons. For a single resonant final state the azimuthal terms turn out to be particularly simple, and may well serve as a test for the spin of the resonance. We show that the angular distribution may be used to detect the possible presence of a p 1/2 resonant state in the energy region of the second resonance. © 1965 Società Italiana di Fisica.